2007
DOI: 10.1111/j.1365-2958.2007.06041.x
|View full text |Cite
|
Sign up to set email alerts
|

Different regions of Mlc and NagC, homologous transcriptional repressors controlling expression of the glucose and N‐acetylglucosamine phosphotransferase systems in Escherichia coli, are required for inducer signal recognition

Abstract: SummaryMlc and NagC are two homologous transcription factors which bind to similar DNA targets but for which the inducing signals and mechanisms of activation are very different. Displacing Mlc from its DNA binding sites necessitates its sequestration to the inner membrane via an interaction with PtsG (EIICB Glc ), while NagC is displaced from its DNA targets by interacting with GlcNAc6P. We have isolated mutations in both proteins which prevent the inactivation of the repressors by growth on glucose or GlcNAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 58 publications
2
56
0
Order By: Relevance
“…The nagB gene was amplified using the following pairs of oligonucleotides, Nag70-Nag72 (NagB-L1), Nag71-Nag72 (NagB-L2), Nag70-Nag73 (NagB-L3), and Nag71-Nag73 (NagB-L4) (Table 2), and inserted as XbaI-EcoRI fragments into pXE1 to give pXE(NagB-L1), pXE(NagB-L2), pXE(NagB-L3), and pXE(NagB-L4). pXE1 is a single-copy R1 replicon plasmid in which expression of the cloned gene is from a promoter within the DNA-derived region of the plasmid expressing the cI857 repressor (16). The whole insert of each NagB plasmid was sequenced with oligonucleotides XE1 and RBP22 (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…The nagB gene was amplified using the following pairs of oligonucleotides, Nag70-Nag72 (NagB-L1), Nag71-Nag72 (NagB-L2), Nag70-Nag73 (NagB-L3), and Nag71-Nag73 (NagB-L4) (Table 2), and inserted as XbaI-EcoRI fragments into pXE1 to give pXE(NagB-L1), pXE(NagB-L2), pXE(NagB-L3), and pXE(NagB-L4). pXE1 is a single-copy R1 replicon plasmid in which expression of the cloned gene is from a promoter within the DNA-derived region of the plasmid expressing the cI857 repressor (16). The whole insert of each NagB plasmid was sequenced with oligonucleotides XE1 and RBP22 (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…EIIB Glc -mediated membrane sequestration was proposed to cause structural restrictions leading to reduced flexibility and therefore to lower affinity for its DNA targets (142). Arg-424 located close to the phosphorylatable Cys-421 in PtsG makes polar contacts with the carboxylate of the C-terminal glycine of Mlc (136,144). Unphosphorylated EIIB Glc prevails when the cells take up glucose.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%
“…We have recently shown, by the use of chimeric proteins, that the H-T-H regions of Mlc and NagC, by themselves, are not sufficient for normal specific Mlc or NagC binding and that the rest of the native protein is necessary for full DNA binding specificity. These studies suggested that the linker between the H-T-H domain and the rest of the protein could be implicated in operator specificity (22). By analogy with the structures of DNA bound to LacI or PurR, we could propose that binding of Mlc or NagC involves amino acid contacts from outside the H-T-H domain, possibly from this unstructured linker, which could form the equivalent of the hinge helix of the LacI-or PurR-operator complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, their C-terminal domains, involved in signal transduction, are quite different, so that the proteins are active under different conditions, and it is thought that amino acids of the ␤-loop wing, adjacent to the H-T-H motif, contribute to the DNA binding site specificity of these two transcription factors (6,48). Mlc and NagC seem to resemble a diverging isorepressor pair, where operator specificity has been achieved without altering the canonical H-T-H interaction, and specific inducing signal recognition occurs, even though the C-terminal domains are still homologous (22). It is interesting that Mlc and NagC control the expression of two PTS transporters, PtsG and NagE, which are themselves homologues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation